The protein phosphatase 2A regulatory subunit B55α is a modulator of signaling and microRNA expression in acute myeloid leukemia cells - Ruvolo, Peter P.; Ruvolo, Vivian R.; Jacamo, Rodrigo; Burks, Jared K.; Zeng, Zhihong; Duvvuri, Seshagiri R.; Zhou, Liran; Qiu, Yihua; Coombes, Kevin R.; Zhang, Nianxiang; Yoo, Suk Y.; Pan, Rongqing; et al. (Biochimica et biophysica acta, 2014)
We recently discovered that the protein phosphatase 2A (PP2A) B55α subunit (PPP2R2A) is under-expressed in primary blast cells and is unfavorable for remission duration in AML patients. In this study, reverse phase protein analysis (RPPA) of 230 proteins in 511 AML patient samples revealed a strong correlation of B55α with a number of proteins including MYC, PKC α, and SRC. B55α suppression in OCI-AML3 cells by shRNA demonstrated that the B subunit is a PKCα phosphatase. B55α does not target SRC, but rather the kinase suppresses protein expression of the B subunit. Finally, the correlation between B55α and MYC levels reflected a complex stoichiometric competition between B subunits. Loss of B55α in OCI-AML3 cells did not change global PP2A activity and the only isoform that is induced is the one containing B56α. In cells containing B55α shRNA, MYC was suppressed with concomitant induction of the competing B subunit B56α (PPP2R5A). A recent study determined that FTY-720, a drug whose action involves the activation of PP2A, resulted in the induction of B55α In AML cells, and a reduction of the B subunit rendered these cells resistant to FTY-720. Finally, reduction of the B subunit resulted in an increase in the expression of miR-191-5p and a suppression of miR-142-3p. B55α regulation of these miRs was intriguing as high levels of miR-191 portend poor survival in AML, and miR-142-3p is mutated in 2% of AML patient samples. In summary, the suppression of B55α activates signaling pathways that could support leukemia cell survival. •B55α is subject to regulation by SRC but acts as a PKC a phosphatase.•The B subunit regulates MYC via competition with another PP2A B subunit.•B55α has a novel role as a regulator of microRNAs in AML.